Akuntansi Dasar di Era Generasi Z pada Siswa/I SMK Techno Media - Sari, Intan Rahma; Muliyani, Muliyani; Winingrum W. A., Sri Putri (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
In this modern era, innovation and dynamic thinking are needed to develop a particular field. The previous generation of people had high hopes for Gen Z to make positive changes in everyday life. The innovations and thoughts of the Gen Z group are often expressed in the professional world. The problems faced by Millennials and Generation Z are almost the same, namely not being able to manage finances properly. A dynamic lifestyle coupled with a lack of knowledge of good financial management makes it difficult for millennials and Z people to manage their finances according to their priority needs. According to the 2021 OCBC Financial Index & Nielsen IQ study, only around 16% of Indonesia's population has an emergency fund. This means that there are still many young people who have not been able to set aside their income for an emergency fund. Even though this emergency fund is very important if something unexpected happens in the future. Another study from Deloitte in 2022 found that nearly half of Gen Z (46%) and Millennials (47%) in the world finance their needs solely relying on their salary that month. The same study found that more than a quarter of Gen Z (26%) and Millennials (31%) in the world are unsure of being able to retire comfortably because the income of the younger generation is used more to finance current living needs and cannot set aside for future needs. . Therefore, today's young generation, to manage and control their finances, really needs the role of accounting in their daily lives. So that the income earned and expenses incurred can be more controlled and can be used as material for self-evaluation of finances as well as for the benefit of the company where they work.